2018
DOI: 10.1111/jon.12574
|View full text |Cite
|
Sign up to set email alerts
|

Diffusely Abnormal White Matter, T2 Burden of Disease, and Brain Volume in Relapsing‐Remitting Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE Multiple sclerosis (MS) diffusely abnormal white matter (DAWM) is a mildly hyperintense magnetic resonance imaging abnormality distinct from typical lesions. Our goal was to investigate the prevalence and natural history of DAWM in a large cohort (n = 348) of relapsing–remitting MS (RRMS) patients. METHODS The presence of DAWM and relationship to changes in T2 burden of disease (BOD), brain volume (brain fractional ratio, BFR), and disability (Expanded Disability Status Scale, EDSS) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…Similar results were found among CIS patients (mean = 2.45, SD = 1.68 and mean = 3.09, SD = 2.34, respectively; P = 0.1). This is in agreement with the notion that DAWM is a phenomenon present in the early stages of the disease 1,7 . It was predominantly detected in posterior periventricular WM, in proximity to focal WM lesions, although it was also found in areas with no visible WM lesions.…”
Section: Resultssupporting
confidence: 92%
“…Similar results were found among CIS patients (mean = 2.45, SD = 1.68 and mean = 3.09, SD = 2.34, respectively; P = 0.1). This is in agreement with the notion that DAWM is a phenomenon present in the early stages of the disease 1,7 . It was predominantly detected in posterior periventricular WM, in proximity to focal WM lesions, although it was also found in areas with no visible WM lesions.…”
Section: Resultssupporting
confidence: 92%
“…Our analysis supports the concept that a slowly progressive increase in T2 lesion volume may be driven by the conversion of DAWM to chronic FWML, and that this phenomenon is not exclusive to SPMS, but is also present in RRMS. We have previously shown that DAWM-to-FWML transformation is more pronounced in SPMS patients that have confirmed disability progression for 12 and 24 weeks 11 . We now extend the findings of this transformation to RRMS, where disability progression independent of relapses is increasingly appreciated to also occur 23 .…”
Section: Discussionmentioning
confidence: 57%
“…However, the image processing pipeline generates robust and consistent results, and it has been previously validated in test-retest settings and used in multi-scanner datasets 11 . Our RRMS cohort is a distinct group, different than the SPMS group, and included patients in very different stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In models of disease involving blood–brain barrier disruption, including brain tumor [ 22 ], brain abscess [ 46 ], subarachnoid hemorrhage [ 47 ], and status epilepticus [ 48 ], Aqp4 null mice develop more severe brain edema than wild-type mice, suggesting that the mode of edema formation (vasogenic versus cytotoxic edema) is important to define the role of AQP4. Edema formation, to a variable extent, has been demonstrated in MS [ 49 , 50 , 51 , 52 ] as well as the EAE [ 53 , 54 ] and cuprizone animal models [ 55 , 56 ]. Comparable to our results, Wolburg-Buchholz and colleagues demonstrated the loss of polarized AQP4 localization in astrocytic end-feet surrounding microvessels during EAE [ 57 ].…”
Section: Discussionmentioning
confidence: 99%